Critical Discourse Analysis (AWK) of Teun A. van Dijk's Model on Online News, Conflict between the Governor of West Java and the West Java DPRD - Rimang, Siti Suwadah; Natasya, Ananda Aulya; Azzahra, Sakinah; Marniati, Marniati (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Mass media plays a crucial role in constructing political conflict discourse through discursive strategies that can influence public perception. The tension between West Java Governor and Regional Representative Council (DPRD) reflects complex local political dynamics where media construction becomes significant in shaping public opinion. Objective: This study aims to analyze how online media constructs the conflict between West Java Governor Dedi Mulyadi and West Java DPRD through Teun A. Van Dijk's Critical Discourse Analysis approach, focusing on macro structure, superstructure, and micro structure in news texts. Method: This research employs qualitative descriptive method with critical discourse analysis. Population and Sample: The population consists of all online news texts discussing the conflict, with one representative news text selected through purposive sampling. Instrument and Data Analysis: The researcher serves as human instrument with Van Dijk analysis table covering three structural levels. Data analysis follows Van Dijk's model encompassing macro structure (topics and subtopics), superstructure (schematic), and micro structure (semantic, syntactic, stylistic, and rhetorical). Results: The analysis reveals that online media is not neutral in constructing political conflict discourse, using pro-executive framing strategies,